Impact of two types of complete pelleted, wild ungulate feeds and two pelleted feed to hay ratios on the development of urolithogenic compounds in meat goats as a model for giraffes. Issue 3 (12th April 2012) - Sullivan, K.; Freeman, S.; van Heugten, E.; Ange‐van Heugten, K.; Wolfe, B.; Poore, M. H.
Summary Urolith formation has been documented in giraffes and goats. As research in giraffes poses logistical challenges, 16 buck goats were used as a model. The impact of two commercially available, pelleted feeds used for giraffes, ADF‐16 and Wild Herbivore (WH), as well as the impact of alfalfa hay and pellet proportions (20% hay:80% pellets, 80P or 80% hay:20% pellet, 20P) on the formation of urolithogenic precursors in goat urine was accomplished in a 2 × 2 factorial balance study. Complete diets contained 0.60, 0.32, 0.35 and 0.26% phosphorus (P) with calcium:P ratios of 1.60, 4.16, 3.06 and 5.23, for 80P‐ADF‐16, 20P‐ADF‐16, 80P‐WH and 20P‐WH respectively. Total faeces and urine were collected over two 5‐day periods to assess N and mineral balance. Fresh urine samples were collected and evaluated microscopically for urolithic crystal content. Urinary nitrogen (N) was lower and N retention was higher in goats fed 80P diets (p < 0.05). Intake of P was greatest for goats fed 80P‐ADF‐16; however, urinary P excretion and P retention were not affected by treatment. Crystal scores were higher in animals receiving 80P diets (p = 0.08), with crystals being composed predominantly of calcium phosphate. Urine pH was alkaline (>8) for all treatments. Urinary P concentration, a risk factor for urolithiasis, was highest (p ≤ 0.06) in the 80P‐ADF‐16 treatment (0.38 vs. 0.01, 0.02 and 0.04 mg/dl for 20P‐ADF‐16, 80P‐WH and 20P‐WH respectively), reflecting its highest dietary P level. Further investigation is recommended to determine the long‐term effects of these diets on urolithogenic compound formation.